2013
DOI: 10.1371/journal.pone.0070104
|View full text |Cite
|
Sign up to set email alerts
|

Potential Reporting Bias in fMRI Studies of the Brain

Abstract: BackgroundFunctional magnetic resonance imaging (fMRI) studies have reported multiple activation foci associated with a variety of conditions, stimuli or tasks. However, most of these studies used fewer than 40 participants.MethodologyAfter extracting data (number of subjects, condition studied, number of foci identified and threshold) from 94 brain fMRI meta-analyses (k = 1,788 unique datasets) published through December of 2011, we analyzed the correlation between individual study sample sizes and number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 35 publications
4
99
0
Order By: Relevance
“…While these lines of evidence suggest that current findings for high-disinhibited women would likely extend to men, follow-up studies examining disinhibition-related differences in fMRI brain response in mixed-gender samples of differing ages are clearly needed before firm conclusions can be drawn. While the sample size of this study is above-average for fMRI studies (David et al, 2013) and of sufficient size to detect relevant effects (Desmond and Glover, 2002), it bears noting that due to the correlational nature of this study, a larger-scale study could have found stronger or additional effects.…”
Section: Discussionmentioning
confidence: 81%
“…While these lines of evidence suggest that current findings for high-disinhibited women would likely extend to men, follow-up studies examining disinhibition-related differences in fMRI brain response in mixed-gender samples of differing ages are clearly needed before firm conclusions can be drawn. While the sample size of this study is above-average for fMRI studies (David et al, 2013) and of sufficient size to detect relevant effects (Desmond and Glover, 2002), it bears noting that due to the correlational nature of this study, a larger-scale study could have found stronger or additional effects.…”
Section: Discussionmentioning
confidence: 81%
“…It is unlikely that these observed discrepancies are due to difference in statistical power, since the sizes of the cohorts essentially were the same. However, increased power of fMRI-studies would generally enhance the overlap of true positive findings (David et al, 2013), and although both studies had cohort sizes within the range of what commonly are used in fMRI studies, the observed discrepancies could reflect a lack of sensitivity that led to the detection of two relatively separate subsets of the true group differences. The divergent findings could possibly also in part be due to the difference in experimental design between the study of Napadow and colleagues (2010) and this study (i.e., here resting-state scans were preceded by task fMRI that potentially introduced spillover effects).…”
Section: Flodin Et Almentioning
confidence: 99%
“…Including original SPMs, as opposed to including only peak regional effects (typically reported in tables of statistics), substantially increases the analyses statistical power 13 and may avoid reporting biases that are likely to affect certain brain regions, especially smaller subcortical regions that are poorly represented in commonly used stereotaxic atlases of the human brain. 15,16 Furthermore, inclusion of this number of SPMs allowed, for the first time, the estimation of the task-specific optimal parameters for processing the peak information of the remaining studies.…”
Section: Introductionmentioning
confidence: 99%